Adat Badamai in the Banjar Community as One of the Alternatives for Criminal Case Resolution - Sudiyono, Sudiyono (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
This article discusses Adat Badamai as a form of dispute resolution commonly practiced by the Banjar community. Adat Badamai refers to the outcome of a deliberative or consultative process aimed at reaching a decision to resolve a problem. In Indonesian criminal law, previously, the resolution of criminal cases always emphasized formal judicial processes, without accommodating alternative methods of dispute resolution outside the judicial process. However, with the ratification of the national criminal law, it is now stated that criminal cases can be resolved outside of judicial proceedings, meaning that if a criminal case is resolved outside the judicial process, the right to pursue legal action is waived, and the case is considered closed. Adat Badamai, which prioritizes a deliberative approach toward consensus, reflects the spirit of the Sultan Adam Law. Under this custom, when a dispute arises—whether civil or criminal—the village elders will take the initiative to bring together the families of the conflicting parties. A ceremony is held, during which the parties exchange apologies, and sometimes a pact is made to prevent further escalation of the dispute. On various occasions, they engage in what is called